Rats with prenatal dexamethasone exposure and postnatal high-fat diet exhibited insulin resistance, and spatial learning and memory impairment: effects of enriched environment. Issue 3 (5th February 2020) - Hsu, Mei-Hsin; Sheen, Jiunn-Ming; Chen, Yu-Chieh; Yu, Hong-Ren; Tain, You-Lin; Huang, Li-Tung
Abstract : This study aimed to examine the combined effects of prenatal glucocorticoid exposure and a postnatal high-fat diet (HFD) on offspring brain development and metabolic disturbance. Besides, the effects of an enriched environment were assessed. Pregnant Sprague–Dawley rats were administered vehicle or dexamethasone between gestation days 14 and 21. Male offspring was then weaned onto either a standard chow or HFD. An enriched environment was implemented between postnatal days 22 and 180 in a subset of rats with prenatal dexamethasone and a postnatal HFD. Adult male offspring with prenatal exposure to dexamethasone and a postnatal HFD showed obesity, increased systolic blood pressure, peripheral and central insulin resistance, and spatial learning and memory impairment detected by Morris water maze. An enriched environment displayed beneficial effects in reducing body weight, decreasing systolic blood pressure, reducing insulin resistance, ameliorating brain molecular alterations, and alleviating spatial deficit in rats with prenatal dexamethasone and a postnatal HFD. In conclusion, adult male offspring with prenatal dexamethasone exposure and a postnatal HFD showed obesity, increased systolic blood pressure, peripheral and central insulin resistance, and spatial learning and memory impairment. In addition, an enriched environment had beneficial effects in this context.